Sexual Self-Disclosure on Adolescents Who Do Porn, Masturbate, and Orgasm (PMO) on Social Media - Put'ri Modu; Arthur Huwae (Kuras Institute, 2023)
PMO stands for porn, masturbation, & orgasm. Many individuals, especially adolescents, have begun to take up sexual pleasure via social media. Reputable studies have noted that individuals who experience sexual experimentation on social media have diverse dynamics and various indications of factors. This study aims to describe the experiences of individuals who have done PMO. Two participants participated through snowball sampling. Data was collected based on semi-structured interviews with the participants. Data analysis was carried out phenomenologically descriptively to see the substance of the PMO experience in the form of themes. This research study obtained 8 PMO themes, including self-limitation, self-control, exploratory behavior, idle curiosity, insecurity, escape coping, fetish, and addiction. The interest of this research is how it can be an effort to will sexual self-disclosure in a more positive way to build self-development.